Novel construction of the catalyst from red mud by the pyrolysis reduction of glucose for the peroxymonosulfate-induced degradation of m-cresol - Chen, Hongliang (Water science and technology : a journal of the International Association on Water Pollution Research, 2022)
Red mud of low cost is regarded as a promising alternative to heterogeneous catalysts for activating peroxymonosulfate (PMS) to degrade m-cresol. Improper valence states of metal oxides and coated active substances in red mud greatly hampered its wide application. To solve this problem, the modified red mud (WRMG/700) was prepared by the pyrolysis reduction of glucose in N2 atmosphere. X-ray diffraction (XRD), scanning electron microscopy (SEM) and X-ray photoelectron spectrum (XPS) analysis confirmed the production of Fe3O4, MnO and NiO in red mud and their gathering on the surface of particles. WRMG/700 exhibited the excellent performance toward PMS activation for the m-cresol degradation with 99.02% degradation efficiency and a pH-independent catalytic activity between initial pH 3-8. The removal efficiency of COD increased with the reaction time under the optimized degradation conditions. The free radical scavenging experiments and electron paramagnetic resonance (EPR) test confirmed 1O2 played a dominant role during m-cresol degradation in the WRMG/700/PMS system, implying m-cresol degradation was a non-radical oxidation process. Accordingly, the possible reaction mechanism was proposed. WRMG/700 retained its activation performance even after five recycles. This study showed a low cost and simple operation process for m-cresol elimination